Health Promotion With Multimedia Methods On Knowledge And Attitude About Risk Dating At Surabaya's Ex-Localization Elementary School - Fatmawati, Elis; Hidayati, Nurul (Jurnal Pendidikan Tambusai, 2021)
The impact of dating leads to deviant behavior resulting in pregnancy. In the preliminary study in the dolly localization work area midwife, there were 2 pregnant patients at the age of 13 and 15 years, where one patient was still a sixth-grade elementary school student. Quasi-experimental research design with Pretest-Posttest Control Design. The sampling technique is Simple Random Sampling with 112 students as respondents. The research site is in the former localization elementary school in Surabaya. Instrument videos and leaflets. Data collection by questionnaire. Bivariate analysis using GLM and Multivariate Analysis using MANOVA. The results of the study showed an increase in knowledge > in the experimental group (22.1), while the control group was 16.5. The attitude of the experimental group is 22.1 > that of the control group, which is 7.6. There is a difference in increasing knowledge about risky dating, namely p-value 0.01 <0.05, and for increasing attitudes about risky dating, P-value 0.00 <0.05. There is an increase in knowledge and attitudes about risky dating in respondents after being given health promotion with multimedia methods. So, the use of additional videos in outreach is very effective.